Metschnikowia pulcherrima as an efficient biocontrol agent of Botrytis cinerea infection in apples: Unraveling protection mechanisms through yeast proteomics - Fernandez-San Millan, Alicia; Fernandez-Irigoyen, Joaquin; Santamaria, Enrique; Larraya, Luis; Farran, Inmaculada; Veramendi, Jon (Biological control, 2023)
[Display omitted] •Metschnikowia pulcherrima Mp-30 prevents Botrytis cinerea infection in apples.•Multiple yeast mechanisms are involved in the gray mold biocontrol ability.•There is a reprogramming of yeast metabolism involved in B. cinerea inactivation.•Membrane trafficking of yeast compounds is enhanced in the fungal presence.•Yeast envelope composition has a major role in the antagonistic interaction. The results obtained in this study show that the Mp-30 strain of Metschnikowia pulcherrima is able to completely prevent Botrytis cinerea infection in apples, which is a major postharvest disease of fruits throughout the world. We have observed that although Mp-30 is able to rapidly colonize wounds, sequestrate iron and secrete antifungal compounds, other unknown mechanisms that occur in the early phase of the yeast-fungal interaction must be implicated in the biocontrol response. The main objective of this study was to identify the pathways involved in the mechanism of action of Mp-30 against B. cinerea in apples. Therefore, differentially accumulated yeast proteins in the presence/absence of B. cinerea on wounded apples were studied to elucidate Mp-30 biocontrol mechanisms and regulation at the protein level. A comparative proteomic analysis showed that 114 yeast proteins were increased and 61 were decreased. The Mp-30 antagonistic response mainly showed the increase of (1) gene expression and protein translation related proteins, (2) trafficking and vesicle-mediated transport related proteins, (3) pyruvate metabolism and mitochondrial proteins related to energy and amino acid production, (4) fatty acid synthesis, and (5) cell envelope related proteins. On the other hand, redox homeostasis, and amino acid and carbon metabolism were downregulated. Since there is no yeast growth enhancement associated with the presence of B. cinerea, such regulation mechanisms may be related to the reprogramming of metabolism, synthesis of new compounds and reorganization of yeast cell structure. Indeed, the results show that several pathways cooperate in restructuring the plasma membrane and cell wall composition, highlighting their major role in the antagonistic interactions for apple protection against gray mold proliferation. These results are of great interest since they provide a clear insight into the yeast mechanisms involved in B. cinerea inactivation during the first hours of contact in the wounded fruit. They shed light on the unknown yeast molecular biocontrol mechanisms.